2018
DOI: 10.3892/ol.2018.7782
|View full text |Cite
|
Sign up to set email alerts
|

miR302a inhibits the proliferation of esophageal cancer cells through the MAPK and PI3K/Akt signaling pathways

Abstract: Abstract. MicroRNAs (miRNAs/miRs) are involved in the regulation of various types of cancer, either as oncogenes or tumor suppressors. miR302a has been reported that it could suppress tumor cell proliferation by inhibiting Akt in prostate cancer. The present study examined the effect of miR302a on proliferation and invasion in esophageal cancer cell lines. The expression levels of miR302a in esophageal cancer cell lines was determined by reverse transcription-polymerase chain reaction. Subsequently, miR302a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(28 reference statements)
0
10
0
1
Order By: Relevance
“…GO term enrichment of biological processes demonstrated that putative miRNA target was the MAPK signaling pathway. Several miRNAs suppressed the MAPK pathway, prohibiting cancer cell proliferation [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…GO term enrichment of biological processes demonstrated that putative miRNA target was the MAPK signaling pathway. Several miRNAs suppressed the MAPK pathway, prohibiting cancer cell proliferation [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…We found 276 co-altered genes for both shRNAs targeting E2F4 ( Figure 6A). 18,19 The MAPK signalling pathway is also studied in AML. The MAPK signalling pathway is a classic cancer-associated signalling pathway involved in the proliferation and differentiation of tumour cells.…”
Section: Overexpression Of Ezh2 Reverses E2f4mediated Inhibition Ofmentioning
confidence: 99%
“…The MAPK signalling pathway is a classic cancer-associated signalling pathway involved in the proliferation and differentiation of tumour cells. 18,19 The MAPK signalling pathway is also studied in AML. 20,21 To determine the specific mechanism of E2F4-induced tumour cell proliferation and differentiation, we further examined the protein levels of MAPK, p-MAPK, ERK and p-ERK when E2F4 expression levels were manipulated in AML cells.…”
Section: Overexpression Of Ezh2 Reverses E2f4mediated Inhibition Ofmentioning
confidence: 99%
“…30 Further to prove the point, overexpression of miR302a inhibited the viability and invasion of esophageal cancer cells via the MAPK and PI3K/AKT signaling pathways. 31 Several studies also reported that the inhibition of MAPK pathway could enhance target sensitivity to tumor Ag-specific CTL lysis, therefore improving the prognosis in esophageal and gastric cancer patients. 32 To the best of our knowledge, this is the first ever report to study the association between MAP3K1 SNPs and ESCC with or without exposure to risk factors.…”
Section: Discussionmentioning
confidence: 99%